ANALISIS TINGKAT KEBIJAKAN DEVIDEN, PENGHINDARAN PAJAK, DAN KINERJA LINGKUNGAN PADA NILAI PERUSAHAAN - Nata, Cahya Amin; Arianti, Baiq Fitri (LPPM Universitas Putera Batam, 2025)
This study aims to determine whether there is an influence of Dividend Policy, Tax Avoidance, and Environmental Performance on Company Value in the basic materials sector listed on the Indonesia Stock Exchange in 2019-2023. In this study, Dividend Policy is measured using the Dividend Payout Ratio by calculating the Retention Ratio first, Tax Avoidance using the Book Tax Difference, Environmental Performance using the Company Performance Rating Program in Environmental Management, and Company Value using Tobin`s Q. This type of research uses quantitative research with secondary data and data sources from the Indonesia Stock Exchange and the websites of basic materials companies listed during the 2019-2023 period. The population of this study is 102 companies and the sample is 8 companies through purposive sampling. The data analysis method used in this study is descriptive statistics, panel data regression analysis, classical assumption testing and hypothesis testing. Data testing in this study uses the Eviews 12 application. The results of this study indicate that Dividend Policy, Tax Avoidance, and Environmental Performance simultaneously affect Company Value, Dividend Policy does not affect Company Value, Tax Avoidance does not affect Company Value and Environmental Performance does not affect Company Value.